Hak Perlindungan Sosial bagi Buruh Migran Informal: Sebuah Perbandingan di Beberapa Negara - Loura Hardjaloka (Jurnal HAM, 2015)
In order to protect informal migrant workers ("BMI"), both sending and receiving countries should provide social protection such as training, mentoring, social security and others as part of the BMI's rights. The obligation to provide social protection for BMI is stipulated in instruments and standards in the international level such as the United Nations Declaration on Human Rights and ILO Convention No. 102 of 1952; and in the ASEAN level. Based on a normative juridical research on the social protection system for BMI in Indonesia and other ASEAN countries, it is found that social protection does not provide maximized yet by not providing social security to the BMI, which is useful to provide compensation and to protect their financial well being. Recent alternative, the government of ASEAN countries requires employers to insure that the employment BMI and BMI can participate voluntarily in the insurance schemes, which are available in the country. Nonetheless, in order to meet human rights of BMI in obtaining social security thus the Indonesian government which is currently revising Law No. 39 Year 2004 concerning the Placement and Protection of Indonesian Workers expected to provide social security scheme for BMI and the implementation of social security can be integrate with the ASEAN countries and other destination countries so BMI can obtain social security benefits wherever they are.